Modulation of neuronal and recombinant GABA(A) receptors by redox reagents - Amato, Alessandra (Blackwell Science Inc, 1999)
1. The functional role played by the postulated disulphide bridge in γ-aminobutyric acid type A (GABA(A)) receptors and its susceptibility to oxidation and reduction were studied using recombinant (murine receptor subunits expressed in human embryonic kidney cells) and rat neuronal GABA(A) receptors in conjunction with whole-cell and single channel patch-clamp techniques. 2. The reducing agent dithiothreitol (DTT) reversibly potentiated GABA-activated responses (I(GABA)) of α1β1 or α1β2 receptors while the oxidizing reagent 5,5′-dithio-bis-(2-nitrobenzoic acid) (DTNB) caused inhibition. Redox modulation of I(GABA) was independent of GABA concentration, membrane potential and the receptor agonist and did not affect the GABA EC(50) or Hill coefficient. The endogenous antioxidant reduced glutathione (GSH) also potentiated I(GABA) in α1β2 receptors, while both the oxidized form of DTT and glutathione (GSSG) caused small inhibitory effects. 3. Recombinant receptors composed of α1β1γ2S or α1β2γ2S were considerably less sensitive to DTT and DTNB. 4. For neuronal GABA(A) receptors, I(GABA) was enhanced by flurazepam and relatively unaffected by redox reagents. However, in cultured sympathetic neurones, nicotinic acetylcholine-activated responses were inhibited by DTT whilst in cerebellar granule neurones, NMDA-activated currents were potentiated by DTT and inhibited by DTNB. 5. Single GABA-activated ion channel currents exhibited a conductance of 16 pS for α1β1 constructs. DTT did not affect the conductance or individual open time constants determined from dwell time histograms, but increased the mean open time by affecting the channel open probability without increasing the number of cell surface receptors. 6. A kinetic model of the effects of DTT and DTNB suggested that the receptor existed in equilibrium between oxidized and reduced forms. DTT increased the rate of entry into reduced receptor forms and also into desensitized states. DTNB reversed these kinetic effects. 7. Our results indicate that GABA(A) receptors formed by α and β subunits are susceptible to regulation by redox agents. Inclusion of the γ2 subunit in the receptor, or recording from some neuronal GABA(A) receptors, resulted in reduced sensitivity to DTT and DTNB. Given the suggested existence of αβ subunit complexes in some areas of the central nervous system together with the generation and release of endogenous redox compounds, native GABA(A) receptors may be subject to regulation by redox mechanisms.